2022
DOI: 10.3389/fmicb.2022.1065313
|View full text |Cite
|
Sign up to set email alerts
|

More microbial manipulation and plant defense than soil fertility for biochar in food production: A field experiment of replanted ginseng with different biochars

Abstract: The role of biochar–microbe interaction in plant rhizosphere mediating soil-borne disease suppression has been poorly understood for plant health in field conditions. Chinese ginseng (Panax ginseng C. A. Meyer) is widely cultivated in Alfisols across Northeast China, being often stressed severely by pathogenic diseases. In this study, the topsoil of a continuously cropped ginseng farm was amended at 20 t ha–1, respectively, with manure biochar (PB), wood biochar (WB), and maize residue biochar (MB) in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In our experiment, the incidence of black rot in continuously cropped soil decreased with increasing biochar dose. Wang et al and Ma et al reported that the concentration of autotoxins in soils is reduced by the addition of biochar and that tobacco growth is promoted [ 29 , 35 ] Therefore, biochar treatment could influence the autotoxin concentration to reduce the DI rate [ 36 ]. β-cembrenediol, din-butyl phthalate, diisobutyl phthalate, ferulic acid, benzoic acid, phthalates and phenolic acids are considered essential autotoxins in tobacco [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, the incidence of black rot in continuously cropped soil decreased with increasing biochar dose. Wang et al and Ma et al reported that the concentration of autotoxins in soils is reduced by the addition of biochar and that tobacco growth is promoted [ 29 , 35 ] Therefore, biochar treatment could influence the autotoxin concentration to reduce the DI rate [ 36 ]. β-cembrenediol, din-butyl phthalate, diisobutyl phthalate, ferulic acid, benzoic acid, phthalates and phenolic acids are considered essential autotoxins in tobacco [ 20 ].…”
Section: Discussionmentioning
confidence: 99%